Relação educação ciência, tecnologia e sociedade e elaboração de programas de ensino - Mezzacappa, Gabriela Gonzales (2013)
STS field of study has been developed as a critic to the conditions of scientific and technological development. Within the propositions of this field there is STS education, which proposes another logic for teaching, through scientifictechnological literacy. Teaching programming technology offers adequate instruments for behavioral changing. STS education also proposes a different teaching logic. Grupo de Estudos em Programação de Ensino e Treinamento (Study Group of Teaching and Training Programming), originated at the collective of consumers ConsumoSol (São Carlos/SP/Brazil), elaborated the description of a problem-situation as part of elaborating a teaching programme of ethic, solidary and responsible consumption for children (aged four to six). This study´s objective was to identify relations between strategies, procedures and discussions of the group and the guidelines of STS education. Analysis elements were estabilished related to the aspects: principles of the STS field (e. g. "Non-linear relations between science, technology and society"), guidelines of scientific-technological literacy (e. g. "Promotion of democracy and participation in STS" and "Problematization of STS at various educative contexts"), challenges and difficulties of the STS education (e. g. "Capacitation of educators" and "Use of scientific language with lay public") and contributions of scientific-technological literacy (e. g. "Educating critic and responsible citizens"). Data were collected using documents, participation of the researcher in the group and audio records. They were systematized in a fluxogram, in which it was possible to identify elements of the four analysis aspects; part of them was related to specific events of the process of elaborating the problemsituation description (such as "Interdisciplinarity", "Promotion of critic to social reality", "Capacitation of educators" and "Use of apprentices´ context informations") and part was identified during the process (such as "Non-linear relations between science, technology and society", "Promotion of democracy and participation in STS", "Integration of interdisciplinary contents" and "Education of critic and responsible citizens"). Some elements were not identified (e. g. "Unveiling of miths of S&T" and "Diversity of theorical and methodological conceptions ). Most part of the elements were related to specific aspects of the process, indicating the potential of using teaching programming technology at group context as an instrument for STS education. Data analysis showed convergences between STS education and the process of describing a problem-situation. New studies may probe the comprehension of these relations and replicate the procedures for data description and analysis, which can be useful for studies at the STS education field.